Evolution of cardio-metabolic risk from birth to middle age the Bogalusa heart study - Berenson, Gerald S.; SpringerLink (Online service). (Dordrecht Springer, 2011)
That precursors of adult coronary artery disease, hypertension, and type II diabetes begin in childhood have been clearly established by the Bogalusa Heart Study. This unique research program has been able to follow a biracial (black/white) population over 35 years from childhood through mid-adulthood to provide perspectives on the natural history of adult heart diseases. Not only do these observations describe trajectories of cardio-metabolic risk variables leading to these diseases but provide a rationale for the need to begin prevention beginning in childhood. The trajectories of the burden of cardio-metabolic risk variables in the context of their fetal origin and chromosome telomere dynamics provide some insight into the metabolic imprinting in utero and aging process. The observed racial contrasts on cardio-metabolic risk variables implicate various biologic pathways interacting with environment contributing to the high morbidity and mortality from related diseases in our population. To address the seriousness of the onset of cardiovascular disease in youth, approaches to primordial prevention are described focussing on childhood health education as an important aspect of Preventive Cardiology.
Foreword -- Preface -- 1. Exploring Chromosomal Leukocyte Telomere Length Dynamics in the Bogalusa Heart Study -- 2. Fetal Origins of Variables Related to Cardio-metabolic Risk -- 3. Trajectories of Variables Related to Cardio-metabolic Risk since Childhood -- 4. Evolution of Metabolic Syndrome from Childhood -- 5. Black-white Divergence in Impaired Fasting Glucose and Type 2 Diabetes Mellitus -- 6. Birth Weight, Stimulus Response and Hemodynamic Variability Implicate Racial (black-white) Contrasts of Autonomic Control of Heart Rate and Blood Pressure and Related Cardiovascular Disease -- 7. Obesity  - Findings from the Bogalusa Heart Study -- 8. Morbid Obesity and Premature Death in the Young -- 9. Target Organ Damage Related to Cardiovascular Risk Factors in Youth -- 10. The Cardiovascular Risk in Young Finns Study and the Special Turku Coronary Risk Factor Intervention Project (STRIP) -- 11. Prevention of Heart Disease in Childhood Rationale for Primordial Prevention -- 12. Dietary Intake of  Children over Two Decades in a Community and an Approach for Modification -- 13. Cardiovascular Health Promotion - Physical Fitness in the School Setting -- 14. Primordial Prevention through School Health Promotion.
Electronic reproduction.
Keywords: Cardiovascular system -- Diseases -- Risk factors; Metabolic syndrome; Cardiovascular system -- Diseases -- Louisiana -- Bogulusa; Coronary disease -- prevention and control; Diabetes mellitus, Type 2.; Gene-environment interaction; Health promotion; Hypertension; Risk factors; Electronic books